2022
DOI: 10.1001/jamanetworkopen.2022.45836
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Exome Sequencing Among Chinese Patients With Hereditary Diffuse Gastric Cancer

Abstract: ImportanceThe E-cadherin gene, CDH1, and the α-E-catenin gene, CTNNA1, were previously identified as hereditary diffuse gastric cancer (HDGC) susceptibility genes, explaining 25% to 50% of HDGC cases. The genetic basis underlying disease susceptibility in the remaining 50% to 75% of patients with HDGC is still unknown.ObjectiveTo assess the incidence rate of CDH1 germline alterations in HDGC, identify new susceptibility genes that can be used for screening of HDGC, and provide a genetic landscape for HDGC.Desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…38-44 NCKAP5 , potentially functioning in microtubule bundle formation and microtubule depolymerization, is less studied, and polymorphisms in this gene are reported to be associated with the clinical outcome of gastric cancer patients in a recent study. 45 Overall, our study suggests different genetic factors controlling tumor onset, multiplicity, metastasis, as well as the site of metastasis.…”
Section: Discussionmentioning
confidence: 73%
“…38-44 NCKAP5 , potentially functioning in microtubule bundle formation and microtubule depolymerization, is less studied, and polymorphisms in this gene are reported to be associated with the clinical outcome of gastric cancer patients in a recent study. 45 Overall, our study suggests different genetic factors controlling tumor onset, multiplicity, metastasis, as well as the site of metastasis.…”
Section: Discussionmentioning
confidence: 73%
“…Germline variants have been found in the MSR1 gene and have been associated with susceptibility to hereditary prostate cancer 26 – 28 and in patients with upper gastrointestinal pathologies such as Barrett’s esophagus and esophageal adenocarcinoma 24 . Germline variants of MSR1 have also been identified rarely in cases of hereditary diffuse gastric cancer 29 and have shown function in M2 macrophage polarization, with emerging functions being seen in tumor-associated macrophages 30 , 31 . Three isoforms exist via alternative splicing of this gene, with isoforms 1 and 2 acting as functional receptors and able to modulate endocytosis of modified low-density lipoproteins (m-LDL) 32 , and isoform 3, a truncated isoform, unable to internalize m-LDL and interestingly capable of acting in a dominant negative fashion when co-expressed with isoforms 1 and 2 31 , 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Literature reports suggest that 30% to 50% of HDGC patients have truncating mutations in CDH1 [ 294 ]. Exome and targeted sequencing results from 284 clinical HDGC patients’ leukocyte samples and paired 186 tumor samples in China showed that the germline mutation rate of CDH1 was only 2.8% [ 295 ], indicating that the genetic susceptibility to HDGC in China may differ from Western countries. Carriers of CDH1 gene mutations have a cumulative risk of developing gastric cancer by the age of 80, estimated at approximately 67% for males and 83% for females.…”
Section: Screening and Diagnosis Of Hereditary Gastric Cancermentioning
confidence: 99%